2021
DOI: 10.1021/acs.jpcc.1c03146
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic View of Laser Fragmentation of Gold Nanoparticles in a Liquid Environment

Abstract: Short-pulse laser irradiation of a colloidal solution of nanoparticles is an effective method for fragmenting the nanoparticles and producing a population of smaller nanoparticles and atomic clusters with properties desired in various fields of applications, including biology, medicine, and catalysis. To investigate the mechanisms involved in the fragmentation, we develop a computational model capable of realistic treatment of a variety of interrelated processes occurring on different time and length scales, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 126 publications
4
41
0
4
Order By: Relevance
“…[33] Note, that in the case of laser post-processing with fs-, ps-, and ns-pulsed lasers in water, the cooling of the nanoparticles from several hundreds and even thousands of Kelvin down to ambient temperature occurs on the time scale of only a few 100 ns [38] after excitation, which leads to many orders of magnitude higher cooling rates in the range of 10 10 K/s. [34] On the other hand, the effective temperature reached during heating by the nanosecond laser pulse increases with the laser pulse intensity. From the degree of inversion reached for the wet-chemical and commercial samples at the highest laser intensity of 1 • 10 12 W m À 2 , an effective temperature around 900 °C can be expected from the comparison to Ref.…”
Section: Chemcatchemmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Note, that in the case of laser post-processing with fs-, ps-, and ns-pulsed lasers in water, the cooling of the nanoparticles from several hundreds and even thousands of Kelvin down to ambient temperature occurs on the time scale of only a few 100 ns [38] after excitation, which leads to many orders of magnitude higher cooling rates in the range of 10 10 K/s. [34] On the other hand, the effective temperature reached during heating by the nanosecond laser pulse increases with the laser pulse intensity. From the degree of inversion reached for the wet-chemical and commercial samples at the highest laser intensity of 1 • 10 12 W m À 2 , an effective temperature around 900 °C can be expected from the comparison to Ref.…”
Section: Chemcatchemmentioning
confidence: 99%
“…[22,23,35,36] After laser heating induced by the pico-or nanosecond laser pulse, the particles rapidly cool down to ambient temperature within ~100 ns (~10 10 K s À 1 ) due to heat transfer from the nanoparticle to the liquid. [34,37,38] Earlier studies on pulsed laser fragmentation have also shown that the size reduction is very often accompanied by a superimposed alteration of the crystal defect density [6,24] and the formation of mixed crystal phases. [25,26] During fragmentation of Co 3 O 4 , [5] CoFe 2 O 4 [25] , and BiFe 2 O 4 [26] , Waag et al observed the occurrence of rocksalt-type CoO, [5] layered double hydroxides, [25] and carbonate impurities.…”
Section: Introductionmentioning
confidence: 99%
“…The defects of AuPt NCs may originate from or could be further intensified by the LFL synthesis process. Re-irradiation of larger NPs initiates a phase explosion, [24,37] followed by sudden cooling of the fragmentation plume, [24] causing the spontaneous solidification in the thermodynamically unfavoured distorted (3 j 1 j 1) surface lattice structure. [21] It has been reported that laser-generated NPs are often defect-rich, caused by cooling rate of 10 12 -10 13 K/s during this kinetically-controlled synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…[21] It has been reported that laser-generated NPs are often defect-rich, caused by cooling rate of 10 12 -10 13 K/s during this kinetically-controlled synthesis. [31] Recently, Zhigilei et al reported that NCs are ejected directly into the dense cold water during LFL, [37] indicating even faster cooling-rates. The distortion depends on the cooling rate, atomic radius, and materialdependent properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation